2017
DOI: 10.21037/gs.2017.05.10
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of metaplastic squamous cell breast cancer: a case report and literature review on surgical management

Abstract: Metaplastic squamous cell breast cancer is an extremely rare subtype, accounting for less than 1% of all invasive breast cancers. As a result, there is sparse data in literature relating to its presentation and management. We report the first known case of metaplastic squamous cell breast cancer which was detected on screening mammogram and followed up as the patient delayed her treatment. This case highlights the aggressive natural behaviour of this subtype and importance of early treatment. The surgical mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Positivity for cytokeratin 5/6 and for CK 34 beta E12 indicate the squamous origin of the neoplasm [ 2 ]. In most cases the tumour is negative for oestrogen and progesterone receptors without Her2/neu overexpression, as found in our patient [ 2 , 10 ].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Positivity for cytokeratin 5/6 and for CK 34 beta E12 indicate the squamous origin of the neoplasm [ 2 ]. In most cases the tumour is negative for oestrogen and progesterone receptors without Her2/neu overexpression, as found in our patient [ 2 , 10 ].…”
Section: Discussionsupporting
confidence: 59%
“…It has not yet proved possible to identify mammographic or ultrasound features that allow an early diagnosis but it has been found that in more than 50% of cases it tends to present as a cystic formation. [ 1 , 10 ]. The pre-operative diagnosis can only be performed by means of a micro-histological examination on needle biopsy [ 1 , 2 ], although only the definitive histological examination can really characterize a state of pure squamous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On ultrasound, the appearance of MBC has been described as a hypoechoic solid mass with mixed cystic and solid components demonstrated as posterior acoustic enhancement ( 1 , 4 ). The definitive preoperative diagnosis of MBC can only be made by means of micro-histological examination through a core-needle biopsy, as it is the only definitive characterization of the pure state of squamous carcinoma ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical management more commonly involves mastectomy as opposed to breast conservation, but this may be due to increased tumour size at presentation and poor response to neoadjuvant chemotherapy and not necessarily increased overall survival or disease-free survival [3]. Conceivably,early diagnosis and treatment could lead to avoidance of mastectomy in some of these patients [6]. In a retrospective review by Dave et al [7], breast conservation surgery for metaplastic cancer was found to be a reasonable treatment option, achieving equal local recurrence free survival and overall survival as compared to mastectomy.…”
Section: Discussionmentioning
confidence: 99%